Assessment and Community Outreach on the Impacts of Citarum River Water Pollution in Batujajar, West Bandung (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
The Citarum River plays a critical role in supporting domestic, agricultural, and industrial needs in West Java. However, increasing anthropogenic activities have significantly degraded its water quality. This study aimed to assess water quality in the Batujajar area, analyze its environmental and health impacts, and promote community awareness through outreach programs. Water samples were collected from 12 observation points and analyzed using physical and chemical parameters, including pH, dissolved oxygen (DO), oxidation-reduction potential (ORP), electrical conductivity (EC), and total dissolved solids (TDS). The results indicate that upstream locations exhibit acidic conditions (pH < 6) and low DO levels (< 4 mg/L), suggesting significant organic pollution. These conditions pose risks to aquatic ecosystems and public health. Community outreach activities were conducted through webinars to enhance public awareness of pollution mitigation strategies. The study highlights the importance of integrating scientific assessment with community engagement to support river restoration efforts.